Penguatan Digitalisasi Pada UMKM Desa Kedungdalem Kabupaten Probolinggo Melalui Pendaftaran Lokasi Usaha Di Google Maps - Dhiya’ Ayu Adibah; Indah Respati Kusumasari (Pusat Riset dan Inovasi Nasional, 2023)
Kedungdalem Village is one of the villages in Dringu District, Probolinggo Regency where one of the most livelihoods of some of the people is traders (MSMEs). One of the problems faced by MSMEs in Kedungdalem Village, Probolinggo Regency is that they have obstacles in the use of digital technology that has not been fully implemented due to lack of public knowledge, especially about the development of digital technology in business implementation. Therefore, the purpose of this service activity is to provide assistance to the community in the use of digital technology in the implementation of their business activities so that later these MSMEs will be able to compete with other online businesses. The method used is qualitative and is implemented through Focus Group Discussion (FGD) activities and assistance in registering business locations on Google Maps. The results obtained from a series of MSME strengthening activities in Kedungdalem Village, Dringu District are an increase in knowledge or awareness from MSME actors in Kedungdalem Village regarding the importance of utilizing digital technology in running a business or business.